Purine nucleotide metabolism regulates expression of the human immune ligand MICA - McCarthy, Michael T.; Moncayo, Gerard; Hiron, Thomas K.; Jakobsen, Niels A.; Valli, Alessandro; Soga, Tomoyoshi; Adam, Julie; O’Callaghan, Christopher A. (The Journal of biological chemistry, 2018)
Expression of the cell-surface glycoprotein MHC class I polypeptide-related sequence A (MICA) is induced in dangerous, abnormal, or “stressed” cells, including cancer cells, virus-infected cells, and rapidly proliferating cells. MICA is recognized by the activating immune cell receptor natural killer group 2D (NKG2D), providing a mechanism by which immune cells can identify and potentially eliminate pathological cells. Immune recognition through NKG2D is implicated in cancer, atherosclerosis, transplant rejection, and inflammatory diseases, such as rheumatoid arthritis. Despite the wide range of potential therapeutic applications of MICA manipulation, the factors that control MICA expression are unclear. Here we use metabolic interventions and metabolomic analyses to show that the transition from quiescent cellular metabolism to a “Warburg” or biosynthetic metabolic state induces MICA expression. Specifically, we show that glucose transport into the cell and active glycolytic metabolism are necessary to up-regulate MICA expression. Active purine synthesis is necessary to support this effect of glucose, and increases in purine nucleotide levels are sufficient to induce MICA expression. Metabolic induction of MICA expression directly influences NKG2D-dependent cytotoxicity by immune cells. These findings support a model of MICA regulation whereby the purine metabolic activity of individual cells is reflected by cell-surface MICA expression and is the subject of surveillance by NKG2D receptor-expressing immune cells.